Glycemic control assessed by continuous glucose monitoring during pregnancy in women with type 1 diabetes and its association with preeclampsia, an observational Swedish cohort study - Linda Englund Ögge; Annika Dotevall; Anders Elfvin; Ulrika Sandgren; Karolina Linden; Linnea Bohlin; Bernadette Wallstersson; Mårten Sjödell; Jaine Augustinsson; Anna Hagman (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Women with type 1 diabetes have an increased risk of preeclampsia (PE), but it is not fully understood if degree of glycemic control is associated with this risk. The aim of this study was to assess glycemic control during pregnancy analyzed by continuous glucose monitoring (CGM) in women with and without PE and to investigate if glycemic control is associated with increased risk of PE. Material and Methods A total of 120 pregnant Swedish women with type 1 diabetes using CGM were included. Background factors and pregnancy outcomes were collected from medical records. CGM data were collected via the internet‐based platform Diasend. Mean glucose, standard deviation of mean glucose, percentage of time in target, time below target, and time above target were presented for each trimester in women who did or did not develop PE. Associations between CGM‐derived metrics and PE were analyzed with logistic regression and adjusted for confounders. Results Twenty‐two women (18.3%) developed PE. There were no significant differences in maternal characteristics between women with and without PE. Glycemic control improved in each trimester but was suboptimal in both groups. Time in target increased from 59% in the non‐PE group and 54% in the PE group in the first trimester to 65% in both groups in the third trimester. There were no significant associations between glycemic control and PE after adjustment for confounders. Conclusions Degree of glycemic control during pregnancy assessed by CGM was not associated with development of PE in women with type 1 diabetes. However, more research is needed to understand the role of glycemic control in relation to development of PE.